Combined severe valvular aortic and valvular pulmonary stenosis and its management - A case report and literature review - Gupta, Amit (Journal of the Saudi Heart Association, 2014)
Isolated congenital valvular stenosis of either aortic or pulmonary valve is commonly seen yet the presence of both these lesions in the same patient is rare. This combination presents unusual diagnostic as well as management problems. Apart from a few case reports, there is little in the literature on the combined stenosis of both semilunar valves. We present here a case report of a three and half year old boy diagnosed as a combined congenital severe valvular aortic stenosis with valvular pulmonary stenosis. The patient underwent successful balloon dilatation of both these valves in the same sitting